Identité et exploitation au travail - Martuccelli, Danilo (SocietàMutamentoPolitica, 2013)
This article explores some aspects of identity exploitation in the world of work. For this, he proceeds in three stages. First, it presents three major forms of capacity of employees - qualification, skills, identities. Then it draws the outlines of specific objective and subjective identity exploitation at work. Finally, it examines the notions of justice and injustice that can be mobilized to account this process.